Photocatalytic Treatment of Shower Water Using a Pilot Scale Reactor - Yash Boyjoo; Ming Ang; Vishnu Pareek (International Journal of Photoenergy)
Treatment of shower water deserves special consideration for reuse not only because of its low pollutant loading but also because it is produced in large quantities. In this study, a pilot scale study of photocatalytic degradation of impurities in real shower water was performed in a 31 L volume reactor using titanium dioxide as the photocatalyst. The reactor was operated in a continuous slurry recirculation mode. Several operational parameters were studied including the slurry initial pH, catalyst concentration, air flow rate, and slurry recirculation rate. Up to 57% of total organic carbon (TOC) elimination was obtained after 6 hours of treatment (for 3.0 slurry initial pH, 0.07 gL−1 catalyst concentration, 1.8 Lmin−1 air flow rate, and 4.4 Lmin−1 slurry recirculation rate). This study showed that photocatalysis could be successfully transposed from bench scale to pilot scale. Furthermore, the ease of operation and the potential to use solar energy make photocatalysis an attractive prospect with respect to treatment of grey water.